The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1177/1049732311420577
|View full text |Cite
|
Sign up to set email alerts
|

Passing Through

Abstract: Breast cancer among Filipinas in the United States is a major but largely neglected cancer disparity. In 2004, a community– university partnership resulted in the first Filipina breast cancer support group in the San Francisco Bay Area. Building on this partnership, we explored the social and cultural contexts of Filipinas’ experiences with breast cancer to inform development of culturally appropriate and sustainable support services and outreach. We utilized multiple qualitative methods (participant observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It is also of importance that we found in this study that religious beliefs and practices provided emotional support for the women to cope with breast cancer. Several researchers have shown that religious practices allow women with breast cancer to cope better, thus enhancing their emotional well-being (Burke, Villero, & Guerra, 2012;Cebeci, Yangın, & Tekeli, 2012;Drageset, Lindstrom, & Underlid, 2010;Harandy et al, 2010;Holt, 2009;Liamputtong & Suwankhong, 2015;Yoo et al, 2010). The women observed Buddhist principles in their lives as a means of dealing with their health condition.…”
Section: Discussionmentioning
confidence: 99%
“…It is also of importance that we found in this study that religious beliefs and practices provided emotional support for the women to cope with breast cancer. Several researchers have shown that religious practices allow women with breast cancer to cope better, thus enhancing their emotional well-being (Burke, Villero, & Guerra, 2012;Cebeci, Yangın, & Tekeli, 2012;Drageset, Lindstrom, & Underlid, 2010;Harandy et al, 2010;Holt, 2009;Liamputtong & Suwankhong, 2015;Yoo et al, 2010). The women observed Buddhist principles in their lives as a means of dealing with their health condition.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has explored cultural differences in survivorship experience and meaning [510]. A growing literature is applying these understandings to the development and implementation of SCPs with the aim of infusing SCPs with the perspectives of patients [1113].…”
Section: Introductionmentioning
confidence: 99%
“…This could be because women in our study included many who were American-born and acculturated, and therefore more aware of resources that allowed them to reach out to others for social support. However, like other studies of Asian American women with cancer, the respondents in our study chose to take care of day-to-day responsibilities by themselves [13, 24]. With the right balance, the women in this study found that caretaking and work created a sense of normalcy that helped them cope with their breast cancer diagnosis and treatment.…”
Section: Resultsmentioning
confidence: 89%